GENETIC MARKERS FOR COGNITIVE DECLINE IN THE ELDERLY - Solé-Padullés, Cristina; Clemente, Imma C.; Bartrés-Faz, David (Anales de Psicología / Annals of Psychology, 2004)
The present paper reviews the studies carried out regarding genetic markers for cognitive decline in the elderly. Specifically, the role of several polymorphisms is studied in the entities of Age Associated Memory Impairment (AAMI) and Mild Cognitive Impairment (MCI), which are considered high-risk conditions for dementia. There are several candiate genes, whose genetic variations appear to modulate some aspect of cognitive functioning, cerebral structure or brain activity within the elder. These genetic polymorphisms are, amongst others, the ones codifying for the following genes: apolipoproteins E and C1, angiotensin-converting enzyme (ACE), endothelial oxide nitric synthase (NOS3), dopamine D2 receptor (DRD2) and serotonin 2A receptor (5HT2A). Behavioural genetics of cognitive ageing requires future methodological developments to investigate with higher reliability the association between genetic variations and neuropsychological function.